2009
DOI: 10.1593/neo.09622
|View full text |Cite
|
Sign up to set email alerts
|

Co-overexpression of Met and Hepatocyte Growth Factor Promotes Systemic Metastasis in NCI-H460 Non-Small Cell Lung Carcinoma Cells

Abstract: Complete resection of early-stage non-small cell lung cancer (NSCLC) is potentially curative, yet approximately 50% of patients are at risk for developing metastatic recurrence. Met, the receptor for hepatocyte growth factor (HGF) is a receptor tyrosine kinase with demonstrated roles in regulating cellular proliferation, motility, morphogenesis, and apoptosis. Met receptor and its ligand, HGF, are commonly overexpressed in NSCLC, and their overexpression has been associated with poor prognosis, which could pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 27 publications
3
47
0
1
Order By: Relevance
“…3B). H460 tumors are highly vascularized (Mukhopadhyay et al, 2002;Navab et al, 2009) but have heterogeneous regions of hypoxia (Lam et al, 2009), in agreement with our findings. AQ4N Is More Toxic to scid Mice Than Nude Mice.…”
Section: Resultssupporting
confidence: 92%
“…3B). H460 tumors are highly vascularized (Mukhopadhyay et al, 2002;Navab et al, 2009) but have heterogeneous regions of hypoxia (Lam et al, 2009), in agreement with our findings. AQ4N Is More Toxic to scid Mice Than Nude Mice.…”
Section: Resultssupporting
confidence: 92%
“…IHC protocols were described previously (32). The staining intensity of CCD68 antibody (Sigma; SAB1103198,1:3000) was scored by a certified pathologist on a scale from 0–3 (0=absent; 1=low; 2=medium; 3=high).…”
Section: Methodsmentioning
confidence: 99%
“…HGF/cMET signaling prevents apoptosis through the phosphorylation of phosphatidylinositol-3-kinase and subsequent Akt activation (12,13). A number of reports have identified that the overexpression of HGF and cMET are associated with cancer invasion, metastasis and poor prognosis in various cancers (14)(15)(16)(17)(18). HGF, known as a scatter factor, is a mesenchymal cytokine with pleiotropic effects, including mitogenic, motogenic and morphogenic properties, and plays an important role in angiogenesis and tumor growth via promoting angiogenic mediators, including vascular endothelial growth factor (VEGF) (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%